Characterization of the Difficult Peripheral IV in the Perioperative Setting: A Prospective, Observational Study of Intravenous Access for Pediatric Patients Undergoing Anesthesia - Heydinger G; Shafy SZ; O'Connor C; Nafiu O; Tobias JD; Beltran RJ (Dove Medical Press, 2022)
Grant Heydinger,1,2 Shabana Z Shafy,1 Colin O'Connor,1 Olubukola Nafiu,1,2 Joseph D Tobias,1,2 Ralph J Beltran1,2 1Department of Anesthesiology & Pain Medicine, Nationwide Children's Hospital, Columbus, OH, USA; 2Department of Anesthesiology & Pain Medicine, The Ohio State University College of Medicine, Columbus, OH, USACorrespondence: Grant Heydinger, Email grant.heydinger@nationwidechildrens.orgBackground: Various criteria exist for defining difficult intravenous access (DIVA) in infants and children. The current study evaluated the factors associated with DIVA in a prospective cohort of over 1000 infants and children presenting for anesthetic care.Methods: This was a prospective, observational study of patients aged 0 to 18 years undergoing elective surgical or radiologic procedures under general anesthesia. Prior to the initial attempt at peripheral intravenous (PIV) cannulation, the anticipated difficulty of PIV catheter placement was determined by the provider using a visual analogue scale (VAS) from 1 to 10. The number of attempts was recorded as well as the time required to achieve PIV access. DIVA was defined as requiring three or more attempts. After successful cannulation, the actual difficulty of the PIV placement was assessed by the provider and recorded using the same VAS. Patient characteristics, including age, race, body mass index (BMI), American Society of Anesthesiologists (ASA) physical classification, and history of difficult PIV placement, were evaluated as covariates.Results: In our cohort of 1002 pediatric patients, 78% of patients were successfully cannulated in a single attempt and 91% of patients were successfully cannulated in two or fewer attempts. Factors associated with requiring three or more PIV attempts included younger age (OR 8.73; 95% CI: 3.38, 22.6 for age < 1 year and OR 4.93; 95% CI: 2.05, 11.8 for age 1- 3 years), higher ASA physical classification (OR 1.95; 95% CI: 1.10, 3.46 for ASA II), and prior history of difficult PIV placement (OR 3.46; 95% CI: 1.70, 7.08). BMI, racial category or gender were not independent predictors of DIVA.Conclusion: We found that approximately 9% of patients required three or more attempts at IV placement in the operating room. Patients that required multiple PIV attempts were more likely to be younger, have a higher ASA classification or a history of difficult PIV placement.Keywords: intravenous cannulation, pediatric anesthesiology, vascular access, peripheral intravenous catheter